Photophysical properties and bioimaging application of an aminonaphthalimide-squaraine non-conjugated system - Stamentović, Vladimir; Collado-Martín, Daniel; Pérez-de-Inestrosa-Villatoro, Ezequiel (Elsevier, 2022)
An aminonaphthalimide-squaraine non-conjugated system was designed and synthetized with the purpose of preparing fluorescent molecule in the 650–700 nm region that could operate via energy transfer (ET) between covalently linked naphthalimide and squaraine chromophores. The photophysical properties of the new fluorescent system were explored with the aim of understanding the ET in one- and two-photon excitation modes. The spectroscopic techniques employed in the characterization includes; absorption, fluorescence, quantum yields and fluorescence lifetime measurements in different solvents. The effect of polarity of solvents on efficiencies of ET were evaluated using one- and two-photon excited fluorescence. The optical behavior of the non-conjugated system was compared with its individual squaraine and naphthalimide moieties. The two-photon absorption (TPA) spectrum of the molecule was obtained between 750 and 1040 nm, with the largest two-photon cross section (δTPA)above 4200 GM. Finally, the applicability of the molecule for fluorescence imaging in the one- and two-photon excitation mode was demonstrated in N13 Microglial cells. The in vitro and in vivo confocal microscopy studies indicated that the non-conjugated system efficiently accumulated in the cytoplasm suggesting it could be utilized as a subcellular probe.
Keywords: Transferencia de energía; Fotones; Squaraine; Naphthalimide; Energy Transfer; Two-photon absorption; Cell bioimaging